Sympathetic denervation of the upper limb improves forearm exercise performance and skeletal muscle bioenergetics. - Kardos, A; Taylor, D; Thompson, C; Styles, P; Hands, L; Collin, J; Casadei, B (2000)
BACKGROUND: Sympathetic activation may limit exercise performance by restraining muscle blood flow or by negatively affecting skeletal muscle metabolic behavior. To test this hypothesis, we studied the effect of thoracoscopic sympathetic trunkotomy (TST) on forearm exercise duration, blood flow, and muscle bioenergetics in 13 patients with idiopathic palmar hyperhidrosis. METHODS AND RESULTS: Heart rate and beat-by-beat mean arterial pressure were recorded at rest and during right and left rhythmic handgrip before and 4 to 7 weeks after right TST. Forearm blood flow was measured bilaterally at rest and on the right during exercise. Right forearm muscle phosphocreatine content and intracellular pH were assessed by (31)phosphorus magnetic resonance spectroscopy. After right TST, exercise duration increased from 8.9+/-1.4 to 13.4+/-1.8 minutes (P<0.0001) with the right forearm and from 5.7+/-0.4 to 7.6+/-0.9 minutes (P<0.05) with the left (P<0.05 for the interaction between treatment and side). Right forearm blood flow at rest was 66% higher (P<0.01) after right TST, but this difference decreased as the exercise progressed. After right TST, a significant reduction occurred in muscle acidification and phosphocreatine depletion during ipsilateral forearm exercise. This was associated with a significantly reduced mean arterial pressure response to right handgrip, whereas the pressor response to left handgrip did not change. CONCLUSIONS: Sympathetic denervation of the upper limb significantly improves forearm skeletal muscle bioenergetics and exercise performance in patients with idiopathic palmar hyperhidrosis.